Optogenetic activation of the reticular nucleus of the thalamus attenuates limbic seizures via inhibition of the midline thalamus. (26th July 2021) - Wicker, Evan; Forcelli, Patrick A.
Abstract: Objective: The nucleus reticularis of the thalamus (nRT) is most studied in epilepsy for its role in the genesis of absence seizures; much less is known regarding its role in other seizure types, including those originating in limbic structures and the temporal lobe. As it is a major source of inhibitory input to higher order thalamic nuclei, stimulation of the nRT may be an effective strategy to disrupt seizure activity that requires thalamic engagement. Methods: We recorded single unit activity from the nRT prior to and after infusion of bicuculline into the area tempestas. We monitored single unit activity time‐locked with interictal spikes. We optogenetically activated the nRT in both the area tempestas and amygdala kindling models. We tested a role for projections from the nRT to higher order midline thalamic nuclei through the use of retrogradely trafficked viral vector. Results: Mean firing rate in the nRT was decreased after infusion of bicuculline into the area tempestas as compared to the preinfusion baseline. nRT unit firing in response to interictal spikes was heterogeneous, with an approximately equal proportion of neurons displaying (1) no change in firing, (2) increased firing, and (3) decreasing firing. Optogenetic activation of the nRT significantly suppressed seizure activity in both the area tempestas and amygdala kindling models. Optogenetic activation of contralaterally targeting projections but not ipsilaterally targeting projections from the nRT to the midline thalamus significantly suppressed seizures in the kindling model. Significance: Although the nRT is typically thought of in the context of absence seizures, our data show that it may be a viable target for other seizure types. In two models that recapitulate the seizure types seen in temporal lobe epilepsy, nRT activation suppressed both electrographic and behavioral seizures. These data suggest that the nRT should be considered more broadly in the context of epilepsy.